1980
DOI: 10.1002/qua.560170408
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic multipole polarizabilities of atomic systems

Abstract: AbstractsTwo previous schemes for the calculation of dynamic multipole polarizabilities of atomic systems, namely, a hydrodynamic analogy to quantum mechanics and a perturbation expansion of the energy in multipoles, follow also from the conventional time-dependent perturbation scheme.Deux procedes, dtcrits prtcbdemment, pour le calcul des polarisabilitts multipolaires dynamiques de systtmes atomiques, savoir une analogie hydrodynamique a la mtcanique quantique et un dtveloppement de perturbation de I'energie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In Table I1 good agreement with that reported by Yousif et al [13]. Recently [15], we have shown that the variational calculation of dynamic multipole polarizabilities of atomic systems using the two schemes namely hydrodynamic analogy to quantum mechanics [ 161 and perturbation expansion of the energy in multipole [ 101 also follow from the conventional time-dependent perturbation scheme [15]. Hence we thought that our calculation for Sl(k) and that using hydrodynamic analogy to quantum mechanics should be the same and the discrepancy between our computed values of S l ( k ) and the given by Shukla et al [14] for k = 0,2,. .…”
Section: Vi(r) = a 2 D F ( R ) K 4 supporting
confidence: 90%
“…In Table I1 good agreement with that reported by Yousif et al [13]. Recently [15], we have shown that the variational calculation of dynamic multipole polarizabilities of atomic systems using the two schemes namely hydrodynamic analogy to quantum mechanics [ 161 and perturbation expansion of the energy in multipole [ 101 also follow from the conventional time-dependent perturbation scheme [15]. Hence we thought that our calculation for Sl(k) and that using hydrodynamic analogy to quantum mechanics should be the same and the discrepancy between our computed values of S l ( k ) and the given by Shukla et al [14] for k = 0,2,. .…”
Section: Vi(r) = a 2 D F ( R ) K 4 supporting
confidence: 90%